2014
DOI: 10.1080/13691058.2014.905707
|View full text |Cite
|
Sign up to set email alerts
|

Concerns about partner infidelity are a barrier to adoption of HIV-prevention strategies among young South African couples

Abstract: As part of a larger study to examine the feasibility and acceptability of a couples-based HIV-prevention intervention, we conducted formative in-depth interviews with 10 couples to explore topics such as challenges in practising safer sex, HIV-prevention strategies, gender power and violence, and issues of trust and infidelity. In this study, both men and women perceived infidelity as ubiquitous in their social context and were therefore unable to discuss HIV risk and prevention without suspicions of infidelit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 24 publications
2
29
1
Order By: Relevance
“…This finding is similar to dynamics observed in Zimbabwe and Malawi where trust, and a belief that condom use would contradict love, constrained safer sex negotiation and practice for married partners ( 51 , 52 ). Parker et al ( 53 ) in South Africa found that concerns about partners’ infidelities, that is, extramarital affairs, were a barrier to safer sex dialogue among couples.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to dynamics observed in Zimbabwe and Malawi where trust, and a belief that condom use would contradict love, constrained safer sex negotiation and practice for married partners ( 51 , 52 ). Parker et al ( 53 ) in South Africa found that concerns about partners’ infidelities, that is, extramarital affairs, were a barrier to safer sex dialogue among couples.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, evidence suggests that couples in primary relationships in SA believe that condoms symbolize distrust and infidelity, and interfere with intimacy. (Mindry et al, 2011; Parker, Pettifor, Maman, Sibeko, & MacPhail, 2014)…”
Section: Discussionmentioning
confidence: 99%
“…Father absence, for example, is well documented in South Africa and persists for a number of reasons, including rural-urban labour migration and denied responsibility of fatherhood (Padi, Nduna, Khunou & Kholopane, 2014). Infidelity and lack of condom use mark many heterosexual relationships (Pettifor, Macphail, Anderson & Maman, 2012), and fear of infidelity drives some unhealthy practices (Parker, Pettifor, Maman, Sibeko & Macphail, 2014).…”
Section: Lack Of Partner Supportmentioning
confidence: 99%